Clinical Impact of Olaparib for Platinum-Sensitive Recurrent Ovarian Cancer - Hiroaki Ishida; Megumi Manrai; Akiko Takashima; Hiroki Egashira; Mizuki Nonaka; Hideaki Shimada (Diseases, 2025)
Background/Objectives: Olaparib, a poly ADP ribose polymerase inhibitor, has been effective in prolonging progression-free survival in platinum-sensitive recurrent ovarian cancer. The clinicopathological factors that predict a favorable prognosis remain unclear. Therefore, we retrospectively analyzed the prognostic effect of clinicopathological factors in the patients treated with olaparib for platinum-sensitive recurrent ovarian cancer. Methods: A total of 16 patients were treated with olaparib from 2018 to 2023. We categorized these patients into the responder (five cases who had not relapsed within 2 years) and non-responder groups (11 cases who had relapsed within 2 years). Clinical factors, including age, number of platinum drug courses, platinum-free interval, and CA125 value before olaparib treatment, were compared between the responder and non-responder groups. Results: The age of the responder group was significantly younger than that of the non-responder group (52 vs. 69 years old, p = 0.02). The CA125 value of the responder group was significantly lower than that of the non-responder group (14.2 vs. 82.7 U/mL, p = 0.02). Conclusions: The good predictive factors that enabled continued olaparib administration without recurrence were younger age and a lower CA125 value before olaparib treatment. The younger group (<65 years old) and the low CA125 value group (<20 U/mL) in PSR may be treated with olaparib for a long period, suppressing disease progression. Providing this information to patients with PSR may help in decision-making regarding performing maintenance therapy with olaparib.